Analisis Kepuasan Mahasiswa Terhadap Pelayanan Institusi Secara Online Pada Masa Pandemi Covid-19 - Kartinasari Ayuhikmatin Sekarjati; Andrean Emaputra; Bekti Utaminingsih (Universitas Medan Area, 2023)
This study aims to analyze the factors of student satisfaction with the services of educational institutions during the Covid-19 pandemic. In December 2019, the issue of the corona virus spread in the world. Until March 2020, the issue of the corona virus reached Indonesia. Several new policies emerged from the Indonesian government based on the development of the corona virus issue, one of which was the service activities of educational institutions which were carried out face-to-face and then carried out non-face to face. Educational institutions are one of the institutions affected by this policy. The object of this research is active students in Indonesia. Data collection was carried out randomly by distributing online questionnaires through a structured evaluation form consisting of several questions to assess non-face-to-face services in educational institutions. Service quality (SERVQUAL) and interest performance analysis (IPA) are used as the methods in this study. Data analysis was performed using SPSS software. There is a gap value of -0.650 from the results of the analysis of service quality in educational institutions. This means that active students in Indonesia are dissatisfied with non-face-to-face services at educational institutions.